2010
DOI: 10.1128/jcm.01582-09
|View full text |Cite
|
Sign up to set email alerts
|

Leukoencephalopathy Associated with Parvovirus Infection in Cretan Hound Puppies

Abstract: Leukoencephalopathies in dogs encompass presumably inherited conditions such as leukodystrophies, hypomyelination or spongiform degeneration, but other causes, such as virus infections and toxic or nutritional factors, might also play a contributory role. In this report, we provide evidence of parvovirus infection and replication in the brains of five 6-week-old Cretan hound puppies suffering from a puppy shaker syndrome and leukoencephalopathy. Although these puppies belonged to two different litters, they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 53 publications
6
29
0
2
Order By: Relevance
“…It is noteworthy that five of twelve samples belonging to this cluster were from brains of puppies with clinical signs of parvovirosis. As already reported, CPV can be detected in the brain in experimental and natural infections [ 9 , 30 ]. The 12 CPV-2b strains account for about 44% of those examined, and they formed a separate cluster in the phylogenetic tree, indicating regional genetic variation of CPV-2 strains [ 17 ].…”
mentioning
confidence: 58%
“…It is noteworthy that five of twelve samples belonging to this cluster were from brains of puppies with clinical signs of parvovirosis. As already reported, CPV can be detected in the brain in experimental and natural infections [ 9 , 30 ]. The 12 CPV-2b strains account for about 44% of those examined, and they formed a separate cluster in the phylogenetic tree, indicating regional genetic variation of CPV-2 strains [ 17 ].…”
mentioning
confidence: 58%
“…Most of the viruses belonging to the Parvoviridae family replicate in mitotically active cells such as intestinal crypt epithelial cells; however, recent studies demonstrated the presence of parvoviruses in typically nonmitotic cells such as neurons. 11,34,36 Furthermore, the pathogenesis of bocaviruses with respect to tissue tropism and replication is not well documented. In this way, the CBoV-2 infection in these puppies resembled that of CBoV-1, which shows viral inclusion bodies in enterocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid phase immune-electron microscopy was performed on a suspension of intestinal sample material using a high titred polyclonal serum against canine parvovirus (CPV). Immunohistochemistry to detect CPV and canine distemper virus (CDV) antigen was performed on sections of small intestine, spleen, lymph node and bone marrow using a monoclonal mouse anti-CPV1-2A1 antibody (Custom Monoclonal Antibodies International, Sacramento, CA) and a monoclonal mouse anti-CDV nucleoprotein antibody (D110, kindly provided by A. Zurbriggen, Berne, Switzerland) as previously described (Schaudien et al, 2010;von Rü den et al, 2012). In addition, to investigate involvement of bacterial agents, a sample of small intestine of one puppy was incubated on standard agar under aerobic and anaerobic conditions (Department of Microbiology, University of Veterinary Medicine Hannover, Germany).…”
Section: Routine Virological Laboratory Diagnosticmentioning
confidence: 99%